Isolation of Ceramides from Tagetes patula L. Yellow Flowers and Nematicidal Activity of the Fractions and Pure Compounds against Cyst Nematode, Heterodera zeae. Issue 6 (28th May 2019) - Bano, Samina; Faizi, Shaheen; Lubna,; Fayyaz, Shahina; Iqbal, Erum Y.
Abstract: Investigation of yellow flower extract of Tagetes patula L. led to the identification of an aggregate of five phytoceramides. Among them, (2 R )‐2‐hydroxy‐ N ‐[(2 S, 3 S, 4 R, 8 E )‐1, 3, 4‐trihydroxyicos‐8‐en‐2‐yl]icosanamide, (2 R )‐2‐hydroxy‐ N ‐[(2 S, 3 S, 4 R, 8 E )‐1, 3, 4‐trihydroxyicos‐8‐en‐2‐yl]heneicosanamide, (2 R )‐2‐hydroxy‐ N ‐[(2 S, 3 S, 4 R, 8 E )‐1, 3, 4‐trihydroxyicos‐8‐en‐2‐yl]docosanamide, and (2 R )‐2‐hydroxy‐ N ‐[(2 S, 3 S, 4 R, 8 E )‐1, 3, 4‐trihydroxyicos‐8‐en‐2‐yl]tricosanamide were identified as new compounds and termed as tagetceramides, whereas (2 R )‐2‐hydroxy‐ N ‐[(2 S, 3 S, 4 R, 8 E )‐1, 3, 4‐trihydroxyicos‐8‐en‐2‐yl]tetracosanamide was a known ceramide. A steroid ( β ‐sitosterol glucoside) was also isolated from the subsequent fraction. The structures of these compounds were determined on the basis of spectroscopic analyses, as well as chemical method. Several other compounds were also identified by GC/MS analysis. The fractions and some commercial products, a ceramide HFA, β ‐sitosterol, and stigmasterol were evaluated against an economically important cyst nematode, Heterodera zeae . Ceramide HFA showed 100 % mortality, whereas, β ‐sitosterol and stigmasterol were 40–50 % active, at 1 % concentration after 24 h of exposure time, while β ‐sitosterol glucoside revealed no activity against the nematode. Abstract :